Culturally Motivated Remembering: The Moderating Role of Culture for the Relation of Episodic Memory to Well-Being. (November 2018) - Wang, Qi; Hou, Yubo; Koh, Jessie Bee Kim; Song, Qingfang; Yang, Yang
Episodic memory for specific personal events is a fundamental human cognitive faculty. Yet it is variably valued across cultures and may thus have different implications for psychological well-being. In a series of studies, we investigated the consequences of cultural fit in detailed episodic recall for psychological well-being among healthy adults and children from European American and East Asian cultural backgrounds. Participants recalled recent and distant personal events (Studies 1, 2, and 3) or recent positive and negative events (Study 4). The findings showed that culture moderated the relation of episodic memory to various aspects of mental health and well-being. Whereas detailed recall was linked to decreased use of avoidant coping among European Americans, it was associated with elevated depressive symptoms, decreased adaptive skills, and increased negative affect among East Asians. The findings support the person-culture-fit framework and suggest that the functional significance of episodic memory depends on cultural contexts.